2016
DOI: 10.18060/18502
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Depression and the Affordable Care Act: Recommendations for Social Work Educators

Abstract: The Patient Protection and Affordable Care Act (ACA) mandates ongoing research on postpartum depression; however, very little research has been published in social work journals and in advanced-level textbooks on this topic. This article describes the problem of postpartum depression and argues that social work educators and researchers must pay greater attention to this issue in light of the ACA mandates, so that social workers can provide effective services to postpartum mothers and their children. The Counc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…These stressful and overwhelming issues may lead many mothers of color to believe their depression is a normal part of motherhood and inhibit them from reaching out for help. Moreover, social workers in all settings have few research studies authored by social workers that are published in social work journals to guide them in their practice (Keefe, Brownstein-Evans, Lane, Carter, & Polmanteer, 2015).…”
Section: Mothers' Experiences With Postpartum Depressionmentioning
confidence: 99%
“…These stressful and overwhelming issues may lead many mothers of color to believe their depression is a normal part of motherhood and inhibit them from reaching out for help. Moreover, social workers in all settings have few research studies authored by social workers that are published in social work journals to guide them in their practice (Keefe, Brownstein-Evans, Lane, Carter, & Polmanteer, 2015).…”
Section: Mothers' Experiences With Postpartum Depressionmentioning
confidence: 99%
“…Despite the fact that social workers have a long-standing history of providing services to mothers and children, there has been little research published in social work journals to guide them in their work with mothers with PPD (Keefe, Brownstein-Evans, Lane, Carter, & Rouland Polmanteer, 2015). Although relevant to the population of mothers living with PPD, research from other professional fields such as nursing and psychiatry is more likely to address individual/biomedical factors such as hormonal fluctuations than to consider issues known to affect maternal and child well-being such as neighborhood safety and domestic violence (Lane et al, 2008).…”
Section: Abstract: Social Work Practice; Postpartum Depression; Matermentioning
confidence: 99%
“…Some of the respondents also reported learning about PPD through empirical literature, including social work journals. We were somewhat stymied by this outcome given the dearth of research reported in social work journals on PPD (Keefe et al, 2015). Although we were pleased to find that some of the responding social workers screen mothers from birth to one year, results from other studies conclude that PPD may not manifest until after one-year post-childbirth (O'Hara & McCabe, 2013;O'Hara & Wisner, 2014).…”
mentioning
confidence: 91%
See 2 more Smart Citations